Dynamics and Control of Machines - Astashev, V. K.; Kolovsky, M. Z.; Babitsky, V. I. (Foundations of Engineering Mechanics, 2000)
Basic models and concepts of machine dynamics and motion control are presented in the order of the principal steps of machine design. The machine is treated as a coupled dynamical system, including drive, mechanisms and controller, to reveal its behavior at different regimes through the interaction of its units under dynamic and processing loads. The main dynamic effects in machines are explained. The influence of component compliances on accuracy, stability and efficiency of the machines is analyzed. Methods for decreasing internal and external vibration activity of machines are described. The dynamic features of digital control are considered. Special attention is given to machines with intense dynamic behavior: resonant and hand-held percussion ones. Targeted to engineers as well as to lecturers and advanced students